AB1298 Prevalence of rheumatic diseases in colombia by city. (12th June 2018) - Londono, J.; Cuervo, F.M.; Rueda, J.C.; Saldarriaga, E.L.; Angarita, I.; Peláez, I.; Forero, E.; Ramirez, J.; Toro, C.; Santos, A.
Abstract : Background: Knowledge of the prevalence of rheumatic diseases allows us to design public health strategies for their comprehensive care and reduction of the costs derived from the potential complications of these diseases. Objectives: To describe and compare the prevalence of rheumatic disease between six cities from Colombia. Methods: The study was developed according the COPCORD epidemiological strategy designed for the identification, prevention and control of rheumatic diseases in developing countries. A cross-sectional analytical study including individuals older than 18 years was designed with a calculated sample size of 6528 people (2336 from Bogotá, 1220 from Medellín and Cali each, 746 from Barranquilla, from Bucaramanga and Cúcuta each one). Prevalence of each rheumatic disease was compared between the evaluated cities from Colombia. Results: A total of 6693 individuals from six cities of Colombia were evaluated. The average age was 46, 40±18, 35 and 4283 (64%) individuals were women. The cities with the highest frequency of positive COPCORD population were Bogotá 36, 6% (n=1813), Cali 19, 1% (n=945) and Medellín 15, 9% (n=789). Abstract AB1298 – Figure 1 The majority of musculoskeletal pain manifested by the population correspond to non-specific muscular discomfort (MMNE). Osteoarthritis (OA) is the most prevalent rheumatic disease (10, 81%, 95% CI, 9, 68–12, 06%). Mechanical low back pain was the most frequent disease in Barranquilla, with a prevalence of 11, 91%, mainly in men 15, 9% (95% CI, 11, 24–21, 92%). Regarding to rheumatoid arthritis (RA) it was more prevalent in women, between 40 and 59 years. It was found to be more prevalent in Bogotá (2, 8%, 95% CI, 1, 8%–4, 1%), Cali (4, 2%, 95% CI, 2, 4–7, 3%) and Barranquilla (1, 5%, 95% CI, 0, 65–3, 23%). Table 1. COPCORD*: Community Oriented Program for Control of Rheumatic Diseases Conclusions: Prevalence of rheumatic diseases is higher in the cities of Bogotá, Cali and Medellin. In Bogotá, Cali and Barranquilla, RA was more prevalent. Low back pain was found to be more prevalent in Barranquilla. The hypothesis is that ethnic diversity of Colombia could explain the difference in prevalence of the rheumatic disease among separate regions. Disclosure of Interest: None declared